Report of the Indian Tariff Board on Additional protection for Galvanized Sheets - Government of India Central Publication Branch (Government of India Central Publication Branch, 1930)
The Tariff Board report examines the need for additional protection for India’s galvanized sheet industry, particularly addressing competition from lower-priced British imports. Initiated at the request of Tata Iron and Steel Company, the inquiry identifies a significant price gap between domestic and imported sheets, exacerbated by falling spelter prices and labor strikes that disrupted production. The Board recommends an additional protective duty of Rs. 37 per ton to stabilize the market and support local manufacturers, arguing that immediate duty adjustments are more effective than bounties previously rejected by the legislature. The report emphasizes the importance of operational efficiency and potential expansion to maintain competitiveness amid prolonged low demand, presenting these measures as vital for ensuring the long-term sustainability and stability of India’s steel sector.
Calcutta: Government of India Central Publication Branch
Keywords: Tariff Board; Galvanized Sheets; Tata Iron and Steel; Import Duties; Foreign Competition; Protective Duty; Steel Industry; Price Differential; Labor Strikes; Market Stability